Dynamic performance analysis of inverter-driven split air conditioner. (October 2020) - Elsayed, Amr Owes; Kayed, T.S.
Abstract: Variable speed technology has a great potential for improving energy efficiency and performance of vapor compression refrigeration cycle. Therefore, the study of dynamic characteristics of the refrigeration cycle using this new technology becomes essential. This study experimentally investigates the dynamic behavior of a split R-410A air conditioner comprising variable speed compressor, variable speed condenser fan, three speed evaporator fan and electronic expansion valve. The characteristics of the conditioner have been presented during the startup and shutdown periods. Furthermore, the effect of changing evaporator fan speed during the running of the conditioner has been illustrated and discussed. The influence of evaporator and condenser inlet air temperatures on the power consumption and coefficient of performance of the conditioner has also been investigated. The experimental results show that increasing the condenser entering air temperature by 7 °C, the power consumption has been increased by 18% and the coefficient of performance decreased by 15%.